Prevalence of eimeria spp. in diarrhoeic calves - Nermin Işık; Özlem Derinbay Ekici (Eurasian Journal of Veterinary Sciences)
Aim: This study was aimed to determine the prevalence of Eimeria spp. in calves in different localities in Konya. Materials and Methods: The study, conducted from January- February 2015, involved 240 faecal samples of calves in the age groups of <1 month, 1-3 months, >3 months in different localities in Konya. Faecal samples were examined by Fulleborn saturated salt floatation technique. After examination of stool, detected oocysts were sporulated in 2.5% potassium dichromate at 22º C and species were identified. Results: Eimeria oocysts were detected as 8.33% in all samples. The positivity rates in each of the age groups were different. According to the age groups (<1 month, 1-3 months and >3 months), the Eimeria spp. were determined as 0.83%, 22.73% and 7.41%, respectively. The highest prevalence was observed in the age group of 1-3 months. E. cylindrica, E. zuernii, E. ellipsoidalis, E. subspherica, E. bovis, E. auburnensis, E. canadensis, E. illinoisensis and E. brasiliensis species were identified in infected calves. Conclusion: In this study, the presence of E. cylindrica, E. zuernii, E. subspherica, E. illinoisensis and E. brasiliensis in calves was firstly demonstrated in Konya province. In particular, the calves in the age group of 1-3 months should be evaluated in terms of coccidiosis and other etiological agents and necessary control measures sholud be taken.